Survey of molecular methods for the typing of wine yeast strains - Schuller, Dorit Elisabeth (2004)
A survey of the genetic polymorphisms produced by distinct methods was performed in 23 commercial winery yeast strains. The microsatellite typing, using 6 different loci, an optimized interdelta sequence analysis and RFLP of mitochondrial DNA generated by the enzyme Hinf I had the same discriminatory power: among the 23 commercial yeast strains, 21 distinct patterns were obtained. Karyotype analysis originated 22 patterns, thereby allowing the discrimination of one of the three strains that were not distinguished by the other methods. Due to the equivalence of the results obtained in this survey, any of the methods can be applied at the industrial scale.